REDUCTION OF ANIONIC SURFACTANT IN DETERJENT FROM DOMESTIC WASTE WATER USING PUMICE AND SAND AS A MEDIA IN CONSTRUCTED WETLAND SYSTEM - Selan, Fianelda Th; de Rozari, Philiphi; Nitbani, Febri Odel; Ola, Pius Dore (Chemistry Notes, 2020)
The use of pumice and sand as a media in Constructed wetland (CW) system to reduce anionic surfactant has been carried out. This research aimed to investigation the efficiency of pumice and sand in CW system with and without plant (cymbopogon citrates) for CW anionic surfactant removal. There were six variation of CW treatments based on percentage pumice amended in the sand media. The anionic surfactant were analysed using UV-VIS spectrophotometry with metilen blue methods. Results of the analysis on oneway anova showed that the efficiency removal of anionic surfactant in inflow and outflow is significant different, on the variation of media of pumice 10% and sand 90% (CW B) reduced anionic surfactant levels efficiently from an average of 0,481 ppm ppm to 0,188 ppm with a decrease in percentage value of 60,91%.